Review of the monograph ‘Intelligent transport systems‘ by Aldona Jarašūniene - Paliulis, Narimantas K. (Transport, 2009)
Review of the monograph ‘Intelligent transport systems‘ by Aldona Jarašūniene, Transport, 24(1), p. 83–84.